Residential environmental livability in Nigeria: an overview - Bashari, Sunusi; Hashim, Ahmad Hariza; Abu Samah, Asnarulkhadi; Ahmad, Nobaya (Center for Promoting Ideas, 2019)
Purpose – The purpose of this paper is to examine the problems of public low-cost housing in Nigeria in relation to residents’ well-being and suggest some guiding principles that can be used for successful public low-cost housing for low-income people in Nigeria. Design/methodology/approach – This research was conducted through in-depth reviews of previous literatures and document related to public low-cost housing in Nigeria. National housing policy is among the document analyzed by the researcher. Findings – The major constraints to public low-cost housing in Nigeria is that, the housing units does not reflect the culture of the resident. Most of the residents are not satisfied with it. The housing units are characterized by indecent housing units, the needs and aspirations of the residents are neglected, high safety and security challenges, poor locational and difficult to access functional facilities. Research limitation / implications – The main limitation of this research is no field survey or interview to collect data from the residents of public low-cost housing has been conducted. Practical Implications – This research will assist housing policy makers and housing developers to understand the important of opinion or views of beneficiaries before and after construction of public low-cost housing. This will be achieve if certain attributes of housing are incorporated in the National Housing Policy as may be suggested by the beneficiaries. Significant to developing countries - Recent studies in Nigeria have shown that, the quality level of building and infrastructural elements depend on cultural background of the beneficiaries. Presently, scholars in Nigeria are shifting towards housing design that will reflect the desire and expectations of beneficiaries through incorporating of culture of the people in housing design. This issue is of great significant to developing countries with different cultural diversities, these differences in culture need to be considered in housing design not adopting standard from developed world. Originality / value – The findings of this paper was based on reviewed of earlier studies on residential environmental livability particularly the public low-cost housing in Nigeria and the analysis of document of National Housing Policy 2012. The findings of this study revealed some guiding principles that can help in solving public low-cost housing problems in Nigeria.